Spatial and temporal analysis of liver cancer mortality in Yunnan province, China, 2015–2019 - Feng, Chengcheng; Liu, Jinghua; Ran, Hailiang; Wu, Linxiong; Liang, Xuemeng; Sun, Hao; Xiao, Yuanyuan; Chang, Wei (Frontiers in Public Health, 2022)
Liver cancer is a major public health challenge. Few published studies reported temporal trend and geographical distribution of liver cancer mortality in China, especially in less developed southwest regions with higher liver cancer incidence. In the current study, we obtained liver cancer mortality data from population-based death surveillance system in Yunnan province in 2015–2019. The mortality of liver cancer was analyzed by using the joinpoint regression model. The space distribution of liver cancer mortality in 129 counties and districts in Yunnan province was illustrated by using the ArcGIS software. Moran's I method was used to estimate the global and local spatial autocorrelation of liver cancer mortality. Analytical results revealed that from 2015 to 2019, the average mortality rate of liver cancer in Yunnan province was 12.96/100,000, with an average annual growth rate of 6.26% (p < 0.05). Higher liver cancer mortality was found in rural areas and in males. Moreover, people aged 45–50 years experienced a steep increase in liver cancer mortality rate. High-high cluster was mainly consisted of areas with higher hepatitis virus infection rate or severe intravenous drug use problem. Our study results suggest a heavy burden of liver cancer in southwest China Yunnan province. Comprehensive intervention measures need to be developed and implemented.